2016
DOI: 10.1021/acs.est.6b04407
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Specific Stable Nitrogen Isotope Values in Avian Tissues: Insights from Captive American Kestrels and Wild Herring Gulls

Abstract: Through laboratory and field studies, the utility of amino acid compound-specific nitrogen isotope analysis (AA-CSIA) in avian studies is investigated. Captive American kestrels (Falco sparverius) were fed an isotopically characterized diet and patterns in δN values of amino acids (AAs) were compared to those in their tissues (muscle and red blood cells) and food. Based upon nitrogen isotope discrimination between diet and kestrel tissues, AAs could mostly be categorized as source AAs (retaining baseline δN va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 52 publications
4
64
1
Order By: Relevance
“…We first analyze the TEFs in AAs between bird and fish bones to preliminarily discuss the tissue‐specific isotopes including AAs isotopes for seabirds and fish. The TEF values (Figures and ) between tropical seabird and flying fish bone AAs δ 15 N or δ 13 C values were quite different from those reported in previous studies of birds (Hebert et al., ; McMahon et al., ). For example, the avian‐specific nitrogen TEF of Glu was higher (TEF Glu = 3.8 ± 0.6‰) in previous study (McMahon et al., ).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…We first analyze the TEFs in AAs between bird and fish bones to preliminarily discuss the tissue‐specific isotopes including AAs isotopes for seabirds and fish. The TEF values (Figures and ) between tropical seabird and flying fish bone AAs δ 15 N or δ 13 C values were quite different from those reported in previous studies of birds (Hebert et al., ; McMahon et al., ). For example, the avian‐specific nitrogen TEF of Glu was higher (TEF Glu = 3.8 ± 0.6‰) in previous study (McMahon et al., ).…”
Section: Discussioncontrasting
confidence: 79%
“…Recently, Hebert et al. () also found that the TDFs based upon the source (Phe) and trophic (Glu) AAs were 4.1 and 5.4 for muscle and red blood cells, respectively, from laboratory and field studies of captive American kestrels and wild herring gulls. This was lower than the values reported for metazoan invertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, we suggest that rather than attempting to sample lower trophic levels by sampling prey species directly, future studies should use a comparative approach and sample species with different diets, but similar scales of movement and geographic distribution of their food sources (Thompson et al, 1995). Alternatively, as compound-specific stable-isotope analyses become more affordable, it will be possible to determine baseline values and thereby more accurately assess trophic-level from within a single tissue sample (McMahon et al, 2015;Hebert et al, 2016;Ostrom et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In order to estimate the fraction of marine protein ( f marine ) in human diets, we used an amino acid nitrogen isotope mass balance model that combines Equations (1) and (2) (see also Hebert et al, 2016; Styring, Fraser, Bogaard, & Evershed, 2014). This approach uses a β mixed value, which multiplies the estimated fraction of marine and terrestrial foods ( f marine and 1‐ f marine , respectively) with their corresponding known marine or terrestrial β values.…”
Section: Discussionmentioning
confidence: 99%